Đáp án:$x = 6;x = \frac{1}{{12}};x = \frac{{ - 19}}{{12}}$
Giải thích các bước giải:
$\begin{array}{l}
\left( {3 - \frac{1}{2}x} \right)\left( {\left| {x + \frac{3}{4}} \right| - \frac{5}{6}} \right) = 0\\
\Leftrightarrow \left[ \begin{array}{l}
3 - \frac{1}{2}x = 0\\
\left| {x + \frac{3}{4}} \right| - \frac{5}{6} = 0
\end{array} \right. \Leftrightarrow \left[ \begin{array}{l}
\frac{1}{2}x = 3\\
\left| {x + \frac{3}{4}} \right| = \frac{5}{6}
\end{array} \right.\\
\Leftrightarrow \left[ \begin{array}{l}
x = 6\\
x + \frac{3}{4} = \frac{5}{6}\\
x + \frac{3}{4} = \frac{{ - 5}}{6}
\end{array} \right. \Leftrightarrow \left[ \begin{array}{l}
x = 6\\
x = \frac{5}{6} - \frac{3}{4} = \frac{1}{{12}}\\
x = \frac{{ - 5}}{6} - \frac{3}{4} = \frac{{ - 19}}{{12}}
\end{array} \right.\\
Vay\,x = 6;x = \frac{1}{{12}};x = \frac{{ - 19}}{{12}}
\end{array}$